2011
DOI: 10.1093/ndt/gfr084
|View full text |Cite
|
Sign up to set email alerts
|

Targeted urine microscopy in Anderson-Fabry Disease: a cheap, sensitive and specific diagnostic technique

Abstract: We investigate the use of wetting films to significantly improve the imaging performance of lensfree pixel super-resolution on-chip microscopy, achieving < 1 µm spatial resolution over a large imaging area of ~24 mm 2. Formation of an ultra-thin wetting film over the specimen effectively creates a micro-lens effect over each object, which significantly improves the signal-to-noise-ratio and therefore the resolution of our lensfree images. We validate the performance of this approach through lensfree on-chip im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 31 publications
3
39
0
1
Order By: Relevance
“…By this technique we were able to identify GL3 in renal podocytes in patients Fabry urine [17]. We suggest that using the examination of urinary sediment with polarised light microscopy may be a useful way to detect Fabry disease particularly in situations where enzyme or genetic analysis is unavailable.…”
Section: Urine Microscopy In Fabry Diseasementioning
confidence: 84%
See 1 more Smart Citation
“…By this technique we were able to identify GL3 in renal podocytes in patients Fabry urine [17]. We suggest that using the examination of urinary sediment with polarised light microscopy may be a useful way to detect Fabry disease particularly in situations where enzyme or genetic analysis is unavailable.…”
Section: Urine Microscopy In Fabry Diseasementioning
confidence: 84%
“…We therefore asked the question "can urine microscopy help, across a wide phenotypic spectrum?" [17].…”
Section: Urine Microscopy In Fabry Diseasementioning
confidence: 99%
“…3) Urine microscopy has demonstrated usefulness in diagnosing FD, as vacuolated epithelial cells, filled with glycosphingolipids, giving the appearance of a 'Maltese cross', can be seen using polarized light microscopy [56]. One report has suggested that screening for mulberry cells (regarded as distal tubular epithelial cells in which Gb3 has accumulated) during urinalysis could be a simple, inexpensive, and non-invasive method for diagnosing this Fabry nephropathy in the absence of proteinuria [57].…”
Section: Biomarkers and Diagnostic Studies For Fabry Nephropathymentioning
confidence: 99%
“…Genotyping can also be useful in male patients to assist with tracing family history of the disease. Urine microscopy may be clinically useful in diagnosing Fabry disease: vacuolated epithelial cells, filled with glycosphingolipids, giving the appearance of a ‘Maltese cross’, can be seen using polarized light microscopy [31]. Assessment of renal Fabry disease involves several assessments and tools (Table 1), with renal biopsy being particularly important to assess and monitor disease progression long term [32].…”
Section: Diagnosis and Assessment Of Fabry Nephropathymentioning
confidence: 99%